Neuronal Cell Death Induces Depressive Disorder in Rats Depression-Like Behaviors Caused by Chronic Stress - Rachmat Hidayat; Mgs Irsan Saleh; Nita Parisa (HM Publisher, 2020)
Introduction: Depression is believed to be a disorder in which an increase in serotonin activity in the brain. This has implications for the development of various antidepressant drugs that work to increase serotonin levels, by inhibiting serotonin reuptake. However, management with antidepressants is still believed to be not optimal, there are still various problems that have not been able to be solved only by increasing serotonin levels in the brain. Therefore, it is necessary to do further exploration to find out other possible pathophysiology of depressive disorders. This study intended to explore the role of apoptosis of neuronal cells in the prefrontal cortex to answer the hypothesis that depression was not only caused by increased serotonin levels but also there was a role of dead neuronal cells in the prefrontal cortex which will trigger the body's homeostatic efforts to compensate by increasing serotonin levels. Methods: A total of 30 male Wistar rats (200 ± 20 g) were obtained from Eureka Research Laboratory (Palembang, Indonesia). Experimental animals were placed in cages under controlled conditions (12 hours of light / dark cycles with temperatures of 22 ± 1˚C and humidity of 40-60%), fed and drank ad libitum. Experimental animals with depression model were induced using Chronic Mild Stress (CMS). CMS procedures were performed with mild stressors such as repeated cold stress (4 ° C), space reduction in the homecage, changed cages and social interaction with other animals of the CMS group. To assess wether animal were being depression or not, the animal were tested using Forced Swimming Test (FST). After induction, rats were randomly divided into two groups which each contained 15 animals: the normal control group (not induced CMS) and the CMS group (negative control). Furthermore, the animal model was performed perfusion to maintain organ when evacuation was done, cell damage did not occur. To evaluate cell organ, immunohistochemistry examination and ELISA examination was performed. All data are presented as mean ± standard deviation and all statistical analyzes are performed with the SPSS 25 (IBM) program. Result: This research showed that CMS animal model has a greater duration of immobility than the normal group and serotonin level in CMS animal models decreased almost threefold compared to the normal group. In addition, there were increased expression of caspase-3 indicates that more neuronal cells suffered from apoptosis. So, in this research, it was clearly stated that in depressive disorder, there were elevation of neuronal cell apoptosis in the prefrontal cortex. Conclusion: Neuronal cell apoptosis in the prefrontal cortex plays a role in the pathophysiology of depression through activation of negative feedback on serotonin production.